Analysis Implementation Strategy Global Operations: A Case Study - Serang, Serlin; Taher, Ardi Mahrifal Hi; Chair, Miftahul; Adrias, Albani Mukti (Journal La Bisecoman, 2025)
This study conducts an SLR of Adidas’ global operational strategies through analysis of 37 scholarly and industry sources between 2000 and 2025. The review groups essential strategic elements into six categories which cover supply chain agility alongside sustainability and Corporate Social Responsibility (CSR), market expansion projects, digital transformations and brand development and internal organizational alignment. Through supply chain decentralization and environmental sustainability integration and technological innovation for customization Adidas has developed a resilient global operation framework. The company maintains its competitive market position abroad through branding efforts which establish cultural meaning and emotional connections with global customers. The current research lacks essential empirical evidence regarding sustainability results and operational branding connections as well as analytical studies about challenges of growth into emerging markets.